Extracting value: mechanistic insights into the formation of natural product artifacts - case studies in marine natural products - Capon, Robert J.
Natural selection relentlessly drives the evolution of natural products, favoring those that enhance the survival of species. During this evolutionary journey, some natural products acquire heightened chemical reactivity towards environmental stimuli, most likely benefiting host species through more agile ecological responses, leading to superior survival outcomes (i.e., more potent and faster acting toxins and chemical defences, infection control, and intra/inter species chemical communication). Although knowledge of natural products informs our understanding of the living world, inspiring new medicines, agrochemicals and scientific tools, the study of chemically reactive natural products can be particularly informative, albeit quite challenging. For example, such natural products are often prone to facile transformations during handling, yielding new "un-natural" products commonly referred to as artifacts. These transformations can be induced by many stimuli, including modest changes in pH or temperature, or exposure to light or air (i.e., oxygen), or even common organic solvents or chromatography media. Sadly, in the race to explore and report on new natural products, knowledge of the relationship between chemically reactive natural products and their artifacts is not always recognised, documented or valued. This review seeks to recalibrate and encourage a greater awareness of the relationship between natural products and artifacts, by examining case studies in the field of marine natural products chemistry (i.e., natural products and associated artifacts from marine invertebrates and algae, and marine-derived microbes). While every effort has been made to provide a comprehensive coverage up to early 2019, any omissions are inadvertent not deliberate. Structured around the types of chemical transformations that can deliver artifacts, and the functional groups involved, the review concludes with observations on how to regulate, detect, rationalise and even exploit artifacts, going forward.